Autochthonous isolate Pseudomonas 42P4 as a sustainable strategy to control Rhizoctonia solani and promote growth of tomato plants - Pérez Rodriguez, María Micaela (2025)
The fungus Rhizoctonia solani is capable of attacking tomato crops leading to great economic losses. Recently, there is the requirement for agricultural strategies to produce and protect crops with a sustainable approach. The integration of Plant Growth-Promoting Rhizobacteria (PGPR) into agricultural practices has emerged as a biocontrol approach. The aim of this work was to evaluate the in vitro antagonistic activity of native PGPR strains from Mendoza (Argentina) against pathogens of tomato seedlings, and the evaluation of the effect of the most effective PGPR by inoculating tomato seedlings infected with R. solani under greenhouse conditions. Pseudomonas 42P4 isolate (Ps 42P4) belongs to the P. corrugata subgroup of the P. fluorescens complex. Ps 42P4 exhibited more biocontrol traits than the rest of the isolates, was able to grow in presence of fungicides and was the most effective strain in reducing in vitro the growth of all pathogens evaluated. The application of Ps 42P4 reduced the disease incidence and severity with respect to the pathogen infected plants and in a similar way to the chemical treatment and the combination of both. Ps 42P4 increased tomato seedling growth under both healthy as well as diseased conditions. The strain keeps the ability to increase overall tomato growth parameters even in combination with the chemical fungicide, under biotic and non-biotic stress. Our evidence suggests that plant protection is due mainly to increasing the antioxidant enzyme activities, and by modulating the profile of phenolic compounds. In conclusion, Ps 42P4 is a potential strain to be considered as a biocontrol agent against R. solani in tomato plants.